Effects of porcine circovirus type 2 vaccine and increasing standardized ileal digestible lysine:calorie ratio on growth performance and carcass composition of growing and finishing pigs - N W Shelton; J L Usry; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A series of 4 experiments was conducted to determine the effect of porcine circovirus type 2 (PCV2) vaccination on the lysine requirement of growing and finishing pigs. Experiments 1 and 2 evaluated the requirement for 85- to 140-lb gilts and barrows, respectively. Experiments 3 and 4 evaluated the requirement for 225- to 275-lb gilts and 215- to 260-lb barrows, respectively. Data from each trial were analyzed as 2 × 4 factorial designs with 2 PCV2 vaccination treatments (vaccinates and non-vaccinates) and 4 levels of increasing standardized ileal digestible (SID) lysine:ME ratio (2.24, 2.61, 2.99, and 3.36 g/Mcal in Exp. 1 and 2 and 1.49, 1.86, 2.23, and 2.61 g/Mcal in Exp. 3 and 4). No PCV2 vaccination × SID lysine:ME ratio interactions were observed (P>0.14) in any of the 4 studies. In Exp. 1 and 2, PCV2 vaccinates had increased (P<0.04) ADG, ADFI, final weight, and daily SID lysine intake and tended to have improved (P<0.09) F/G compared with non-vaccinates. In Exp. 1, ADG and F/G improved (quadratic; P<0.03) as the SID lysine:ME ratio increased, with increases through 2.99 g/Mcal. In Exp. 2, increasing the SID lysine:ME ratio improved (linear; P<0.001) F/G and increased (linear; P<0.001) daily SID lysine intake and SID lysine intake per pound of gain. Thus, 3.36 g SID lysine/Mcal ME appears to maximize efficiency for 85- to 140-lb barrows. In Exp. 3, PCV2 vaccinates had improved (P<0.02) F/G and increased (P<0.03) final weight, SID lysine intake per pound of gain, and backfat thickness compared with non-vaccinates. Both ADG and F/G improved (quadratic; P<0.05) as the SID lysine:ME ratio increased, with ADG improving through 1.86 g/Mcal and F/G improving through 2.23 g/Mcal, indicating the requirement may be between those levels. In Exp. 4, both ADG and ADFI were decreased (P<0.04) in vaccinates compared with non-vaccinates. In this study, ADG, F/G, daily SID lysine intake, and SID lysine intake per pound of gain increased (linear; P<0.001) and F/G improved (linear; P<0.001) through the highest level of 2.61 g lysine/Mcal, with the greatest magnitude of change when lysine was increased from 2.23 to 2.61 g/Mcal. Because of the lack of any interactions between dietary SID lysine level and PCV2 vaccination, it appears that PCV2 vaccination did not increase the lysine requirement for growing and finishing barrows and gilts. On the basis of these studies, which used corn-soybean meal-based diets with 3% added fat, the requirement was 1.04% SID lysine or 1.17% total lysine for 85- to 135-lb gilts, 1.17% SID lysine or 1.31% total lysine for 85- to 140-lb barrows, 0.78% SID lysine or 0.88% total lysine for 225- to 275-lb gilts, and 0.91% SID lysine or 1.02% total lysine for 215- to 260-lb barrows.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Amino acid requirements; Lysine; Porcine circovirus type 2 (PCV2) vaccine; Swine